Rekonstruksi Hukum Terhadap Kebijakan Penyelenggara Pemerintahan Nagari Dalam Masyarakat Heterogen Di Sumatera Barat (Studi Pada Nagari Gagut Di Kabupaten Agam) - Delfina Gusman; Alsyam Alsyam (University Of Bengkulu Law Journal, 2023)
The Nagari Government is the lowest government and the implementation of the Nagari government is based on the traditions and socio-culture of the people of West Sumatra. The form of the Nagari Government has been regulated through the West Sumatra Provincial Regulation Number 7 of 2018 concerning Nagari. The development that occurs from a homogeneous society to a heterogeneous society has the potential for social change both internally and externally. This social change is influenced by various factors, including population transmigration, marriage, and the economy that forces people to settle in the area. The increase in heterogeneous society certainly gives rise to heterogeneous villages in West Sumatra. The results of the first study, the form of legal construction of the village administration policy can be done in an argumentum a contrario. This legal construction is the right model where in order to achieve all the interests of the community in the local nagari, legal discovery can be made by agreement (buek arek) with due regard to local wisdom. Second, the policies in the Nagari Government are special and different from the general village regulations and are based on the values ​​that have been integrated into the Nagari environment..